Pengaruh Kualitas Produk dan Citra Merek terhadap Kepuasan Konsumen Melalui Keputusan Pembelian Sebagai Variabel Intervening - Anwar Virgano Fauzi; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study was to determine the effect of product quality and brand image on consumer satisfaction through the decision to purchase Vans shoes in Wonosari City. The population in this study are all Vans shoe users in the city of Wonosari whose number is unknown. Sampling used using the formula for calculating the Hair sample, so that a total sample of 114 respondents was obtained. The data analysis technique used is descriptive statistical analysis method, classical assumption test, multiple regression analysis, and hypothesis testing. The results of this study indicate that product quality and brand image have a positive and significant effect on purchasing decisions. Purchase decisions have a positive effect on consumer satisfaction. Product quality and brand image have a positive and significant effect on consumer satisfaction